1991
DOI: 10.1161/01.res.68.5.1179
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial alpha 1-adrenoceptors mediate positive inotropic effect and changes in phosphatidylinositol metabolism. Species differences in receptor distribution and the intracellular coupling process in mammalian ventricular myocardium.

Abstract: Species-dependent variations of myocardial ca1-adrenoceptor-mediated positive inotropic effects of epinephrine were assessed in relation to characteristics of ael-receptor bindings and acceleration of phosphatidylinositol metabolism in the isolated rat, rabbit, and dog ventricular myocardium. Epinephrine in the presence of the /3-adrenoceptor antagonist bupranolol (10-6 M) elicited a positive inotropic effect through activation of ael-adrenoceptors in rat and rabbit, whereas in dog ventricular myocardium, bupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 54 publications
1
53
0
1
Order By: Relevance
“…The effects of a1-adrenoceptor agonists and endothelin-l were also inhibited by PDBu or PMA (Kushida et al, 1988;Endoh et al, 1991;. It is noteworthy that the inhibitory action of PDBu was selective for the inotropic effect associated with phosphoinositide hydrolysis: the basal force of contraction, and the inotropic effects of isoprenaline and Bay K 8644 were scarcely affected by PDBu.…”
Section: [ §X Y'mentioning
confidence: 94%
See 2 more Smart Citations
“…The effects of a1-adrenoceptor agonists and endothelin-l were also inhibited by PDBu or PMA (Kushida et al, 1988;Endoh et al, 1991;. It is noteworthy that the inhibitory action of PDBu was selective for the inotropic effect associated with phosphoinositide hydrolysis: the basal force of contraction, and the inotropic effects of isoprenaline and Bay K 8644 were scarcely affected by PDBu.…”
Section: [ §X Y'mentioning
confidence: 94%
“…It was not shown whether the maximal response to All in the presence of losartan (0.1-1 JAM) could reach that of control, because of the availability of All. On the other hand, the nonpeptide AT2 receptor selective antagonist, PD 123319 (1 JAM) did not influence the PIE of All (Figure 3b Influence of PDBu on the positive inotropic effect and phosphoinositide hydrolysis induced by angiotensin II Previously we have found that the phorbol esters, phorbol 12-myristate 13-acetate and PDBu, antagonize selectively the PIE mediated by myocardial ax-adrenoceptors or endothelin receptors that was elicited in association with acceleration of phosphoinositide hydrolysis in the rabbit papillary muscle (Kushida et al, 1988;Endoh et al, 1991;. Therefore, we examined the influence of PDBu on the PIE of All.…”
Section: Drugs Usedmentioning
confidence: 96%
See 1 more Smart Citation
“…This action is closely related to its negative chronotropic action. However, Endo et al (1991) have demonstrated that an acceleration of phosphatidylinositol metabolism and positive inotropic action in response to the activation of a,-adrenoceptor stimulation occurred in rat hearts. The same mechanism could be involved in the rat cardiac conduction system, because Tung et al (1985) have shown a positive chronotropic response induced by a,-adrenoceptor stimulation in rat isolated atria.…”
Section: Discussionmentioning
confidence: 96%
“…It could be argued, however, that it may not be safe to extrapolate animal data to humans and that, in particular, rodents' hearts have a much greater density of ␣-adrenergic receptors than primates' hearts. 16 Indeed, the use of ␣-adrenoceptor blockers in patients with heart failure has in the past not been accompanied by demonstrable benefits. Nonetheless, the accepted notion that ␣-blockers fail to provide any significant benefit or may even be harmful in heart failure is largely based on the results of studies using older, short-acting agents 17 that were administered without ␤-blockers, the use of which was at that time not recommended.…”
Section: Discussionmentioning
confidence: 99%